2019
DOI: 10.1016/j.addbeh.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation as a correlate of cannabis use and problem use

Abstract: Objective: Cannabis users with a dysregulatory risk factor may be particularly vulnerable to engaging in more frequent and problematic cannabis use. Contemporary models of dysregulated behavior suggest that dysregulation emerges due to distinct mechanisms. The current study seeks to examine the dysregulatory correlates of cannabis involvement, including working memory capacity, delay discounting, impulsivity, and reward sensitivity.Method: Participants were 104 non-treatment seeking frequent cannabis users (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 97 publications
(91 reference statements)
3
25
0
Order By: Relevance
“…The rise in cannabis use is concerning because it is linked to biopsychosocial impairments characteristic of Cannabis Use Disorder (CUD; Budney, 2006;Hasin et al, 2013;Volkow et al, 2014). Like other substances, cannabis use is thought to be driven by imbalances between a deliberative neural system that mediates cognitive control and future valuation, and a reactive system that facilitates reward and emotional processes (Kim-Spoon et al, 2019;Lopez-Vergara et al, 2019). This approach posits that maladaptive decisions either occur through failures of selfregulation, the exertion of control (top-down) over reflexive processes to achieve long-term goals (Bickel et al, 2012), or through impaired emotion regulation, the adaptive control of one's emotional processes (bottom-up; Bickel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The rise in cannabis use is concerning because it is linked to biopsychosocial impairments characteristic of Cannabis Use Disorder (CUD; Budney, 2006;Hasin et al, 2013;Volkow et al, 2014). Like other substances, cannabis use is thought to be driven by imbalances between a deliberative neural system that mediates cognitive control and future valuation, and a reactive system that facilitates reward and emotional processes (Kim-Spoon et al, 2019;Lopez-Vergara et al, 2019). This approach posits that maladaptive decisions either occur through failures of selfregulation, the exertion of control (top-down) over reflexive processes to achieve long-term goals (Bickel et al, 2012), or through impaired emotion regulation, the adaptive control of one's emotional processes (bottom-up; Bickel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CU as a contributor to anhedonia has been proposed as a path whereby CU may contribute to depression (5,78). Several studies have reported apathy and anhedonia in cannabis users (81)(82)(83), while others failed to detect this phenomenon (84)(85)(86). Decreased cerebral activation in response to reward is reduced in cannabis users, and more so in those with recent heavy CU (87).…”
Section: Influence Of Cannabis On the Course And Clinical Presentation Of Depressionmentioning
confidence: 99%
“…Relative to the effect sizes observed in the aforementioned drug classes, the relationship between delay discounting and cannabis use is unclear (Strickland et al 2020). While there is evidence that delay discounting is associated with cannabis use frequency and severity (Aston et al 2016;Kim-Spoon et al 2019;Lopez-Vergara et al 2019;Sofis et al 2020), there have also been null findings (Dennhardt et al 2015;Heinz et al 2013;Johnson et al 2010;Peters et al 2013). A recent meta-analysis found that the relationship between delay discounting and cannabis did not differ from other substances (Amlung et al 2017).…”
Section: Introductionmentioning
confidence: 99%